Inducible nitric oxide synthase expression is increased in the brain in fatal cerebral malaria. - Maneerat, Y; Viriyavejakul, P; Punpoowong, B; Jones, M; Wilairatana, P; Pongponratn, E; Turner, G; Udomsangpetch, R (2000)
AIMS: Nitric oxide (NO) has been hypothesized to play a major role in the pathogenesis of cerebral malaria caused by P. falciparum infection. NO may act as a local neuroactive mediator contributing to the coma of cerebral malaria (CM). We hypothesized that increased expression of inducible nitric oxide synthase (iNOS) may cause increased release of NO, and examined the expression and distribution of iNOS in the brain during CM. MATERIAL AND RESULTS: Brain tissues from fatal cases of cerebral malaria in Thai adults were examined using immunohistochemical staining to detect iNOS. The distribution and strength of staining was compared between 14 patients with CM, three of whom were recovering from coma, and controls. iNOS expression was found in endothelial cells, neurones, astrocytes and microglial cells in CM cases. There was also strong staining in macrophages surrounding ring haemorrhages. iNOS staining was decreased in recovering malaria cases compared to acute CM, and was low in controls. Quantification showed a significant association between the intensity and number of iNOS positive vessels with the severity of malaria related histopathological changes, although the total number of cells staining was not increased compared to recovering CM cases. CONCLUSIONS: This study indicates that an acute induction of iNOS expression occurs in the brain during CM. This occurs in a number of different cells types, and is increased in the acute phase of CM compared to cases recovering from coma. As NO may activate a number of secondary neuropathological mechanisms in the brain, including modulators of synaptic function, induction of iNOS expression in cerebral malaria may contribute to coma, seizures and death.